USE D-OPTIMAL MIXTURE DESIGN IN FORMULATION OF ONCHIDIID SLUG (ONCHIDIUM TYPHAE) INSTANT POWDER AS FUNCTIONAL FOODS - Wijianto, Bambang; Tendianus, Tendianus; Pratiwi, Liza (Jurnal Farmasi Sains dan Praktis, 2024)
Onchidiid slug (Onchidium typhae) is an animal with bioactive compounds with high nutritional value and the potential to be used as a functional food product. The study aimed to optimize the onchidiid slug instant powder formula, analyze its proximate content, and determine its hedonic level. The formula of instant powder was made with a comparison of the composition of maltodextrin and dextrose based on the run in the D-Optimal Mixture Design (DMD) program, namely run 1 (20%:10%), run 2 (10%:20%), run 3 (13.33%: 16.67%), run 4 (16.67%:13.33%), run 5 (15%:15%), run 6 (12.5%:17.5%), run 7 (10%: 20%), run 8 (20%:10%). The powder is tested for water content and dissolution time, and the optimal formula is analyzed using One Sample T-Test in SPSS. The results showed that the composition of maltodextrin and dextrose significantly affected the characteristics of instant powder. The optimal instant powder formula combines 18.690% maltodextrin and 11.310% dextrose with a water content of 4.892% and a soluble time of 118.052 seconds. The results of statistical analysis in verifying the optimal formula show a p-value > 0.05 (not significant). The results of the proximate content test were 8.21% water content, 0.42% ash content, 0.85% crude fiber, 3.54% protein, and 1.54%. They had a preference level in the like and acceptable in terms of color, taste, texture, and scent.